Green synthesis and antifungal activity of Al2O3 NPs against fluconazole-resistant Candida spp isolated from a tertiary care hospital. Issue 109 (11th November 2016) - Jalal, Mohammad; Ansari, Mohammad Azam; Shukla, Arun Kumar; Ali, Syed G.; Khan, Haris M.; Pal, Ruchita; Alam, Javed; Cameotra, Swaranjit Singh
Abstract : Antifungal activity of ecofriendly and cost effectively prepared Al2 O3 NPs on Candia alibicans . Abstract : Eco-friendly and cost effective Al2 O3 NPs were synthesized by a green method using a leaf extract of Cymbopogon citratus . The characterization of the synthesized NPs was performed by XRD, HR-TEM, EDS, AFM, DLS, and zeta potential. To our knowledge, for the first time, the antifungal activity of Al2 O3 NPs against various Candida spp isolated from oropharyngeal mucosa of HIV + patients has been investigated. The antifungal potential of Al2 O3 NPs has been assessed by determining minimum inhibitory concentrations (MIC), minimum fungicidal concentration (MFC), growth kinetics, and well diffusion methods. The minimum concentration at which Al2 O3 NPs inhibit the growth of Candida spp were 250–500 μg ml −1 and more or less no growth has been observed at higher concentration ( i.e., 1500 μg ml −1 ) when incubated for 48 h. The mechanisms of Al2 O3 NPs– Candida cell biointerface interaction and its intracellular localization were further characterized by SEM and HR-TEM. The electron microscopic analysis shows that Al2 O3 NPs not only attach to the surface but also penetrate inside the Candida cells and disrupt the morphological as well as physiological activity that led to the death of the cells. Due to the scavenging potential of Al2 O3 NPs, the antifungal activity of Al2 O3 NPs is mild towards tested yeast spp and that is why these NPs suppressed the growth of yeast cells at higher concentration. The result obtained in this study shows that Al2 O3 NPs inhibit the growth of fluconazole susceptible and fluconazole resistant C. albicans and C. dubliniensis in a similar manner regardless of their drug resistant mechanisms. Thus, the present study revealed that Al2 O3 NPs may be a promising remedy for the development of anticandidal agents and play an important role for sustained controlled drug delivery in medical implants and for therapeutic coatings on implantable devices used in orthopedics and dentistry.